PHYSICAL CHARACTERISTICS OF ULTISOLS AND THE IMPACT ON SOIL LOSS DURING SOYBEAN (Glycine max Merr) CULTIVATION IN WET TROPICAL AREA - Yulnafatmawita, Yulnafatmawita; Adrinal, Adrinal (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
Physical characteristicsare among soil propertiesaffecting the susceptibility to erosion.Â Determination of physical characteristics of Ultisol was aimed to evaluate the dynamics of soil properties as well asthe impact on soil erosion and runoff (RO) during soybean cultivation in wet tropical area.Â Soybean was planted within erosion plots (18 m2)Â at 25% slope in UltisolLimauManis (having > 5000 mm annual rainfall).Â Â Soil samples for physical properties (soil texture, bulk density, total pore, permeability, aggregate stability,and organic carbon) as well as amount of RO and soil loss were analyzed at 5 different times (stages) during the cultivation.Â The results showed that there was fluctuation in physical properties of Ultisol during the cultivation. Likewise, the amount of runoff and soil loss also changed during the study.Â Among the physical properties analyzed, the aggregate stability index of the soil highly correlated to the amount of RO (R2=0.73) and soil loss (R2=0.94).Â Amount of RO and soil loss was controlled by soybean development at the average rainfall intensity â¤ 36 mm/day, but not at rainfall intensity >36 mm/day. Â It is suggested not to open heavily clayey-low OC soils for seasonal crop farming during rainy season in wet tropical area.Â Keywords: soil physical properties, Ultisol, erosion,runoff, soybean cultivation